Áreas urbanas inundáveis, perspectivas de gestão nos contextos francês e brasileiro - Sergio Torres Moraes (Confins)
The study of the different structure of government organization in Brazil and in France for the management of the territory - especially regarding the vulnerability of inhabited areas to natural events - can contribute to the debate related to the risk of occupation of vulnerable areas. It is notorious that the persistence of the problem is a consequence of failed or neglected urban development policies in considering the risks of occupying non-propitious areas in the land use plans. In both countries the search to structure a complex organization of the territory relies on a universe of legal instruments, which are not always enough to achieve the "right to the city" to its inhabitants. In the case of urban areas subject to natural events risk, an effort is being made to create specific instruments to achieve a democratic management of the cities' environment and to protect the population at risk. In this study, we seek in the concept of "resilience" a theoretical support to discuss the relationship between public policies and their effects on territories vulnerable to flood risk.